<span>Assuming the graph is y=-3(√2x)-4 and y=-3√(x-4) the transformation would be:
</span><span>The graph is compressed horizontally by a factor of 2
x=1/2x'
</span>y=-3(√2x)-4
y=-3(√x')-4 <span>
</span><span>moved left 4
x=x'-4
</span>y=-3(√x)-4
y=-3(√x'-4)-4
<span>
moved down 4
y=y'-4
</span>y=-3(√x-4)-4
y'-4=-3(√x'-4)-4
y'=-3(√x'-4)-4 +4
y'=-3(√x'-4)
Answer: C. <span>The graph is compressed horizontally by a factor of 2, moved left 4, and moved down 4.
</span>
Answer:
c. x=3
Step-by-step explanation:
Given:
7x < 21
Divide both sides by 7
7x / 7 < 21 / 7
x < 21/7
x < 3
x = 3
Check:
7x < 21
7(3) < 21
21 = 21